Menciptakan Home Literacy bagi Anak Usia Dini di Era Digital - Nurhayati, Eti; Ulfah, Maulidya (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
There has been a change of family in this digital era such as the structure, roles, and responsibilities of parents in early childhood education, including in literacy. The change will continue to occur in family life, but parental responsibility together in child care and education is an ideal condition that must be created in the family, which is not replaced by the technology in this digital era. This paper aims to: (1) identify some changes in family life in the digital era, (2) offer home literacy programs for early childhood in the digital era, including: the urgency of developing literacy for early childhood, the role of parents in home literacy, creating home literacy, and implementing home literacy. Home literacy is an alternative solution for early childhood in developing potential in his/ her golden age. The role of parents in home literacy are to provide means and facilities, to design the environment at home, and actively to engage in literacy activities as a mentor or friend in the activity.